2003
DOI: 10.1053/rapm.2003.50029
|View full text |Cite
|
Sign up to set email alerts
|

Lateral branch blocks as a treatment for sacroiliac joint pain: A pilot study

Abstract: In patients with SI joint pain who respond to L4-5 dorsal rami and S1-3 LBB, RF denervation of these nerves appears to be an effective treatment. Randomized, controlled trials are needed to further evaluate this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
141
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(151 citation statements)
references
References 19 publications
(27 reference statements)
5
141
0
4
Order By: Relevance
“…Eight of nine patients had more than 50% pain relief that lasted for more than nine months 16 . Ferrante et al reported use of radiofrequency denervation with bipolar electrodes for thermoablation along the sacroiliac joint line.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Eight of nine patients had more than 50% pain relief that lasted for more than nine months 16 . Ferrante et al reported use of radiofrequency denervation with bipolar electrodes for thermoablation along the sacroiliac joint line.…”
Section: Resultsmentioning
confidence: 96%
“…Histological analysis of the sacroiliac joint has verified the presence of nerve fibers within the joint capsule and adjoining ligaments. It has been variously described that the sacroiliac joint receives its innervation from the ventral rami of L4 and L5, the superior gluteal nerve, and the dorsal rami of L5, S1, and S2, or that it is almost exclusively derived from the sacral dorsal rami 5,7,12,13,14,15,16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…When selecting patients, neither double comparative blocks nor prognostic lateral branch blocks have proved to enhance outcomes. Studies in cadavers have demonstrated that the L5−S3 levels should be targeted in most people, although some individuals may benefit from lesioning L4 and S4 as well [21,22]. Indirect evidence has shown that cooled probe technology can enhance lesion size, and may this improve treatment outcomes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data on the efficacy of PRF are limited, whereas there is a stronger evidence for CRF, not only with respect to pain relief but also in terms of functional restoration (21)(22)(23)(24)(25). Additionally, most reports are retrospective in nature and have involved only small patient groups.…”
Section: Discussionmentioning
confidence: 99%